2017
DOI: 10.1080/13678868.2017.1340075
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the motivation and willingness of self-initiated expatriates, in the civil engineering industry, when considering employment opportunities in Qatar

Abstract: This paper provides empirical and contextual insight into the complexity of Self-Initiated Expatriates' (SIEs) experiences in a unique setting. Factors that influence SIEs in the civil engineering industry, when considering overseas employment in Qatar, are identified and considered. Drawing comparison to organisational expatriates (OEs) and builds on the work of Doherty, Dickmann, and Mills (2011), this paper uses semistructured interviews conducted with professionals from the civil engineering and constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 70 publications
(108 reference statements)
0
17
0
Order By: Relevance
“…However, recent work (e.g. Altman and Shortland, 2008; Harrison and Michailova, 2012; Kapiszewski, 2017; Metcalfe, 2007; Ridgway and Robson, 2017; Rodriguez and Scurry, 2014; Scurry et al, 2013) has shifted the focus towards the role of structures and arrangements in host countries, exploring the tensions unfolding amid the increasing presence of women expatriates in neo-patriarchal regions, such as the Middle East. For instance, in their study of expatriates in Qatar, Rodriguez and Scurry (2014) identified that expatriates experienced career capital stagnation and hurdles associated with formal and informal institutions (e.g.…”
Section: Expatriate Workers In the Gcc: The Role Of Gendered Institutmentioning
confidence: 99%
“…However, recent work (e.g. Altman and Shortland, 2008; Harrison and Michailova, 2012; Kapiszewski, 2017; Metcalfe, 2007; Ridgway and Robson, 2017; Rodriguez and Scurry, 2014; Scurry et al, 2013) has shifted the focus towards the role of structures and arrangements in host countries, exploring the tensions unfolding amid the increasing presence of women expatriates in neo-patriarchal regions, such as the Middle East. For instance, in their study of expatriates in Qatar, Rodriguez and Scurry (2014) identified that expatriates experienced career capital stagnation and hurdles associated with formal and informal institutions (e.g.…”
Section: Expatriate Workers In the Gcc: The Role Of Gendered Institutmentioning
confidence: 99%
“…For many countries, expatriation is of paramount importance, especially because it brings in knowledge and talent from abroad, strengthening the competitive advantages of regions and cities within countries ( Ridgway and Robson, 2018 ), and it may even improve a country’s global economic status ( Caligiuri and Bonache, 2016 ). Many countries therefore adopt national and regional strategies to attract talent, as is the case, for example, in the Gulf State of Qatar, where highly skilled expatriates are attracted from Europe, North America, Australia, Egypt, Jordan and the Philippines.…”
Section: Introductionmentioning
confidence: 99%
“…This research conducted over the past two decades has identified two main types of expatriation: self-initiated expatriation (SIE) and assigned expatriation (AE) ( Andresen et al, 2014 ; Pinto and Caldas, 2015 ; Farcas and Goncalves, 2017 ). Studies have sought to make better sense of these types of expatriation by studying, in particular, individual motivations to expatriate ( Suutari and Brewster, 2001 ; Hippler, 2009 ; Lee and Kuzhabekova, 2018 ; Ridgway and Robson, 2018 ). Perhaps because individual motivations to expatriate to a specific country reflect the country-level factors that attract talent ( Ridgway and Robson, 2018 ), identifying these factors may thus help countries establish effective strategies to attract more talented individuals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations